Necessity of Including Forensic Accounting in Accounting Programs in Sudanese Universities - Elseed, Eltayeb Mohammed Suliman Fadl; Khalid, Waleed Eltayeb Omer (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to demonstrate the necessity of including Forensic accounting in accounting programs in Sudanese universities in order to upgrade an accounting knowledge, and to limit failure of the accounting programs to build an accountant who specializes in courts and litigation affairs. This present study used descriptive and analytical approach to analyze the data collected through a questionnaire from accounting faculty members, and judges in Sudan. The study reveals that there is a great need to include Forensic accounting in accounting programs that help increase the effectiveness of external auditing and improve the performance of supervisory bodies in financial institutions. Furthermore, the main challenges that may be faced by institutions for inclusion of Forensic accounting are the lack of response of educational systems in Sudan and absence of specific standards, academic bodies, or institutions. This study proposes the necessity of including Forensic accounting in accounting programs at the bachelor’s level as a freelance specialization, urging research centers to shed lights on it, and include the authorities who are concerned with establishing well programs.